1995
DOI: 10.1080/09670269500651051
|View full text |Cite
|
Sign up to set email alerts
|

Application of polymerase chain reaction (PCR) using random amplified polymorphic DNA (RAPD) primers in the molecular identification of selectedSargassumspecies (Phaeophyta, Fucales)

Abstract: The random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) was used for the molecular characterisation and identification of Sargassum spp. A total of 17 samples of Sargassum (Sargassaceae, Fucales) was obtained from various localities around Peninsular Malaysia and Singapore. On the basis of morphological characteristics, the samples were tentatively grouped into five species: Sargassum baccutaria, S. glaucescens, S. aligacystum, S. polycystum and S. siliquosum. By RAPD-PCR, five of 31 random p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Random amplified polymorphism DNA (RAPD) (Williams et al, 1990;Hadrys et al, 1992) was used successfully in species differentiation on Gracilaria (Meneses, 1996;Lim et al, 2001), Furcellaria (Valatka et al, 2000), Laminaria (Billot et al, 1999) and Sargassum (Ho et al, 1995a(Ho et al, , 1995bPark et al, 1998;Engelen et al, 2001). The objective of this study is to use a combination of morphometric and RAPD analyses to differentiate between the S. baccularia and S. polycystum, which are found in close proximity.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Random amplified polymorphism DNA (RAPD) (Williams et al, 1990;Hadrys et al, 1992) was used successfully in species differentiation on Gracilaria (Meneses, 1996;Lim et al, 2001), Furcellaria (Valatka et al, 2000), Laminaria (Billot et al, 1999) and Sargassum (Ho et al, 1995a(Ho et al, , 1995bPark et al, 1998;Engelen et al, 2001). The objective of this study is to use a combination of morphometric and RAPD analyses to differentiate between the S. baccularia and S. polycystum, which are found in close proximity.…”
Section: Introductionmentioning
confidence: 97%
“…There are more than 400 species of Sargassum, described primarily using morphological characters (Ho et al, 1995a). Sargassum is highly differentiated with variable phenotypes based on several factors including environment and locality.…”
Section: Introductionmentioning
confidence: 99%
“…The DNeasy Plant Mini Kit was found to be unsuitable for Gracilaria, as it could not efficiently remove the polysaccharide. This was also observed with Sargassum, which has alginic acid (Ho 1995a;Wong et al 2004). This can be overcome by using only the tips of Gracilaria that are freshly ground using liquid nitrogen.…”
Section: Discussionmentioning
confidence: 52%
“…2). Previous work using RAPD on Gracilaria and Sargassum species in the Algae Research Laboratory, University of Malaya, showed good reproducibility (Ho et al 1995a;Gan 1999;Lim et al 2001). Major bands were observed to be constant with all the amplifications, but minor bands were more variable.…”
Section: Molecular Analysismentioning
confidence: 91%
“…Recently, RAPD was used in genotoxicity studies (Atienzar et al 2000;Atienzar and Jha 2006) and in discriminating genetically modified organisms (Cheah and Radu 2006). RAPD was used successfully in species differentiation for seaweeds, namely, Gracilaria species (Martinez et al 1999;Lim et al 2001), Sargassum species (Ho et al 1995a(Ho et al , 1995bPark et al 1998;Engelen et al 2001;, Postelsia (Coyer et al 1997), Hizikia fusiformis (Park et al 1998), Laminaria (Billot et al 1999;Yotsukura et al 2001) and Furcellaria lumbricalis (Valatka et al 2000). The objective of this study is to use RAPD to differentiate between (a) the S. binderi and S. oligocystum, and (b) S. baccularia, S. polycystum and S. stolonifolium.…”
Section: Introductionmentioning
confidence: 99%